2007
DOI: 10.1016/j.neuroscience.2007.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regional and subcellular localization of adenylyl cyclases type 1 and 8 in mouse brain

Abstract: Adenylyl cyclases (ACs) convert ATP to cAMP and therefore, subserve multiple regulatory functions in the nervous system. AC1 and AC8 are the only cyclases stimulated by calcium and calmodulin, making them uniquely poised to regulate neuronal development and neuronal processes such as learning and memory. Here, we detail the production and application of a novel antibody against mouse AC1. Along with AC8 immunohistochemistry, these data reveal distinct and partially overlapping patterns of protein expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 34 publications
5
79
0
Order By: Relevance
“…These compartmentalized effects of AC8 and AC1 also fit with recent evaluations of the subcellular localization of AC1 and AC8 protein. Although the domains are somewhat overlapping, AC1 and AC8 localize to primarily postsynaptic and presynaptic compartments, respectively (Conti et al, 2007).…”
Section: Camp and Presynaptic Potentiationmentioning
confidence: 99%
“…These compartmentalized effects of AC8 and AC1 also fit with recent evaluations of the subcellular localization of AC1 and AC8 protein. Although the domains are somewhat overlapping, AC1 and AC8 localize to primarily postsynaptic and presynaptic compartments, respectively (Conti et al, 2007).…”
Section: Camp and Presynaptic Potentiationmentioning
confidence: 99%
“…Compared with AC1, whose activity is regulated by both G-proteins and Ca, AC8 is a pure Ca sensor. Recently, we found that the endogenous AC1 is preferentially localized in the postsynaptic density, whereas AC8 is detected mainly in the presynaptic active zone (Conti et al, 2007) (Fig. 7).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, we found that the endogenous AC1 was mainly localized at the postsynaptic density (PSD). The endogenous AC8 was preferentially concentrated at the presynaptic active zone (PAZ) (Conti et al, 2007). These findings suggest that AC1 and AC8 may play distinct roles in regulating activity-dependent plasticity.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations